A Lysosome‐Activated Tetrahedral Nanobox for Encapsulated siRNA Delivery (Adv. Mater. 46/2022). Issue 46 (17th November 2022) - Gao, Yang; Chen, Xingyu; Tian, Taoran; Zhang, Tao; Gao, Shaojingya; Zhang, Xiaolin; Yao, Yangxue; Lin, Yunfeng; Cai, Xiaoxiao
Abstract : DNA Nanotechnology Tetrahedral framework nucleic acids have attracted extensive attention as a static drug nanocarrier. In article number 2201731, Xiaxiao Cai and co‐workers report a dynamic lysosome‐activated tetrahedral nanobox for completely encapsulating short interfering RNA. The closed tetrahedral structure endows cargo RNA with active release. This work offers a dynamic pH‐sensitive confinement delivery system for small RNA.